Metabotropic Glutamate Receptors: Potential Drug Targets for the Treatment of Schizophrenia - Chavez-Noriega, L.E.; Schaffhauser, H.; Campbell, U.C. (Current Drug Targets-CNS & Neurological Disorders, 2002)
Schizophrenia is a debilitating chronic psychiatric illness affecting 1% of the population. The cardinal features of schizophrenia are positive symptoms (thought disorder, hallucinations, catatonic behavior), negative symptoms (social withdrawal, anhedonia, apathy) and cognitive impairment. Although progress in elucidating the aetiology of schizophrenia has been slow, new insights on the neurochemical and neurophysiological mechanisms underlying the pathophysiology of this illness are beginning to emerge. The glutamate / N-methyl-D-aspartate (NMDA) hypofunction hypothesis of schizophrenia is supported by observations that administration of NMDA glutamate receptor antagonists such as phencyclidine (PCP) or ketamine induces psychosis in humans moreover, decreased levels of glutamate and changes in several markers of glutamatergic function occur in schizophrenic brain. Administration of PCP or ketamine to rodents elicits an increase in locomotion and stereotypy accompanied by an increase in glutamate efflux in several brain regions. Systemic administration of group II metabotropic glutamate (mGlu) receptor agonists suppresses PCP-induced behavioral effects and the increase in glutamate efflux. Activation of group II mGlu receptors (mGlu2 and mGlu3) decreases glutamate release from presynaptic nerve terminals, suggesting that group II mGlu receptor agonists may be beneficial in the treatment of schizophrenia. In addition, pharmacological manipulations that enhance NMDA function may be efficacious antipsychotics. Selective activation of mGlu5 receptors significantly potentiates NMDAinduced responses, supporting this novel approach for the treatment of schizophrenia.The glutamate hypothesis of schizophrenia predicts that agents that restore the balance in glutamatergic neurotransmission will ameliorate the symptomatology associated with this illness. Development of potent, efficacious, systemically active drugs will help to address the antipsychotic potential of these novel therapeutics.This review will discuss recent progress in elucidating the pharmacology and function of group II mGlu and mGlu5 receptors in the context of current hypotheses on the pathophysiology of schizophrenia and the need for new and better antipsychotics.
Keywords: m glur2